Epidemiological study of facial fractures in a brazilian subpopulation (Research, Society and Development, 2021)
Facial injuries, including bones fractures that comprise them, assume a prominent role in the care of polytrauma patients in general emergencies, often leading to severe psychomotor and social sequelae to those affected. Objective: To survey the victims’ epidemiological data of oral and maxillofacial trauma treated at the Hospital de Base Luis Eduardo Magalhães in Itabuna / BA. Methods: A hundred and eight medical records were used, totaling 147 fractures. The analyzed data were gender, age, the city in which the patient resides, etiology of the fracture and its location, being tabulated, organized, and described using the Microsoft Excel and Word program (version 2016). Results: there was a male predominance (76.27%); the most prevalent age group was between 24 and 34 years old, with 32 being the most repercussions and 47.5 years being the average age. The mandible was the most affected bone, representing 34.01%, with motorcycle accidents as the primary etiology and Itabuna the city with the most patients. Conclusion: with young adults being the most affected patients and traffic accidents, especially motorcycles, as the primary etiology, it is noted that such fractures could be avoided with the increase of more educational measures in traffic and greater punishment for reckless drivers makes it is essential in reducing such pathology.